Urgensi Wakaf Produktif Dalam Pembangunan Ekonomi Masyarakat - Dewi Sri Indriati (Jurnal Ilmiah Al-Syir'ah, 2017)
Strategies that can be developed to empower this productive zakat, ranging from legal products to building networks in the form of productive investment partnerships. One is money endowments that can open up unique opportunities to create investments to provide religious services, educational services, and social services. Nazhir has an important role in managing endowments property in accordance with what is desired by the endowments and can be benefited by the community then Nazhir must have programs work both short-term programs and long-term programs. In order to develop endowments productively, the government established Badan Wakaf Indonesia (BWI) which has the purpose to coordinate with Nazhir and the development of national and international endowments management. The medium and long-term program is to develop existing Nazhir institutions to be more credible (professional and trustworthy) so the institutions should be directed, nurtured and given stimulus (stimulus) so that the endowments property can be developed productively.